Influence of Business Process Maturity Model as a Business Architecture Planning Proposal - Zaleha Fauziah; Dedeh Supriyanti; Sulistiawati (ADI Publisher, 2021)
This research is a part of previous research that succeeded in producing business model architecture planning, the purpose of this study was to develop previous research using the measurement method of business model maturity as a proposed business model architecture planning concept. By taking the same case study theme as the Tiara Payung Putra (TPP) company. TPP is known as a distributor company in cooperation with Pertamina (Bulk LPG Freight and Filling Station). TPP's main business activity is distributing goods in the form of LPG to 76 bases spread across Balaraja district. The current condition of the business model architecture illustrates the business activities that exist in the TPP. The main problems that occur in TPP are not integrating external systems with internal business activities in the company, and lack of IT resource support. For this reason, the Business Process Maturity Model is needed as a benchmark, which can be proposed as a business architecture planning concept. The business process maturity model process is supported by data validation obtained through respondents, namely business stakeholders in TPP, the process for validating the data by distributing the Assessment questionnaire consisting of 8 Parts the Business Process Assessment model, and 3 Parts for IT Application Readiness Assessment. support of the Enterprise Architecture Planning (EAP) Framework method which focuses on the business model architecture domain. The architecture of the business model illustrates how TPP carries out business activities and functions to achieve its objectives. The results of this study produce the proposed business model architecture planning concept in the form of Business Model Maturity Level Measurement, the IS / IT architecture concept, and the Business Architecture Planning roadmap, which are beneficial for the Tiara Payung Putra (TPP) company for the business model architectural planning